Identification of locally advanced rectal cancer with low risk of local recurrence. - Qiao-Xuan Wang; Shao-Hua Li; Xu Zhang; Lan Xie; Pei-Qiang Cai; Xin An; Zhi-Zhong Pan; Pei-Rong Ding (PLoS ONE, 2015)
Background The routine application of neoadjuvant chemoradiotherapy for T3N0 rectal cancer remains controversial. The aim of this study was to use clinical, Magnetic resonance imaging, and pathological parameters to identify a subgroup of patients with low risk of local recurrence who might be precluded from neoadjuvant chemoradiotherapy. Methods We retrospectively reviewed a prospectively maintained database of consecutive rectal cancer patients who underwent curative resection. 166 pathologic confirmed T3N0 rectal cancer patients with tumor located 5-12 cm above the anal verge and preoperative circumferential resection margin >1 mm were included in analysis. The primary outcomes measured were 3- and 5-year local recurrence rates. Results Local recurrence was demonstrated during follow-up in 5 patients; the actuarial overall 3- and 5-year local recurrence rates were 2.5% and 3.4%, respectively. Inadequate sampling of lymph nodes (≤12) was associated with higher local recurrence (P = 0.03) in this group of patients. Conclusion For upper and middle T3N0 rectal cancer with preoperative circumferential resection margin >1 mm, local recurrence rate after total mesorectal excision is low and surgery alone may be enough for this group of patients.